2007
DOI: 10.1128/ec.00073-07
|View full text |Cite
|
Sign up to set email alerts
|

Internal and Surface-Localized Major Surface Proteases ofLeishmaniaspp. and Their Differential Release from Promastigotes

Abstract: Major surface protease (MSP), also called GP63, is a virulence factor of Leishmania spp. protozoa. There are three pools of MSP, located either internally within the parasite, anchored to the surface membrane, or released into the extracellular environment. The regulation and biological functions of these MSP pools are unknown. We investigated here the trafficking and extrusion of surface versus internal MSPs. Virulent Leishmania chagasi undergo a growth-associated lengthening in the t 1/2 of surface-localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
1
35
0
1
Order By: Relevance
“…The release of internal, but not surface-oriented, MSPs from promastigotes of L. chagasi incubated with the extracellular matrix increased at normal mammalian body temperature (37°C) but not at room temperature. Conversely, the release of surface-localized MSPs increased at room temperature but was inhibited at 37°C (106). Release of MSP at 37°C could facilitate close contact between promastigotes and host cells such as Mø and fibroblasts and thus could be favorable for parasite entry and/or long-term survival.…”
Section: Msp's Role In the Pathogenesis Of Leishmaniasismentioning
confidence: 99%
See 2 more Smart Citations
“…The release of internal, but not surface-oriented, MSPs from promastigotes of L. chagasi incubated with the extracellular matrix increased at normal mammalian body temperature (37°C) but not at room temperature. Conversely, the release of surface-localized MSPs increased at room temperature but was inhibited at 37°C (106). Release of MSP at 37°C could facilitate close contact between promastigotes and host cells such as Mø and fibroblasts and thus could be favorable for parasite entry and/or long-term survival.…”
Section: Msp's Role In the Pathogenesis Of Leishmaniasismentioning
confidence: 99%
“…These experiments revealed that one-fourth of the nascent MSPs remained internally for up to 6 days following biosynthesis, strongly supporting the existence of a stable internal subpopulation of MSPs. It appeared that only the mature 63-kDa form, not the 59-kDa protein, accounts for this subpopulation of internal MSPs (106,109). We have not formally ruled out two less likely possibilities: (i) that some surface MSP isoforms are inaccessible to surface biotinylation due to the presence of densely packed LPG, a situation reminiscent of the failure of immunogold to label some MSPs on the cell surfaces of L. major promastigotes (86), and (ii) that MSPs are constantly internalized with biotin removal.…”
Section: "Abnormal" Msps Of Leishmanial Promastigotes: Functions Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…release proteolytically active gp63 into the extracellular medium presumably facilitating the propagation of the parasite [131,132].…”
Section: Leishmania Spp Gp63mentioning
confidence: 99%
“…contains multiple MSPs and can be found on the promastigote surface as well as in the parasite cytoplasm. Surface MSP is involved in parasite development within sandfly and the cytoplasmic MSP which is in preformed form is ready to use by the mammalian host (Yao, Donelson et al 2007). This action is analogous to various effectors that are used by type III secretion system in bacteria which behaves like syringe and needle to inject various factors into cells (Winnen, Schlumberger et al 2008).…”
Section: Host Cells For Leishmania Parasitesmentioning
confidence: 99%